The 2020 Update on Pressure Injuries: A Review of the Literature. (January 2022) - Saindon, Kelley; Berlowitz, Dan
Abstract : GENERAL PURPOSE: To provide an update on the epidemiology, pathophysiology, prevention, and patient preferences for care of pressure injuries (PIs). TARGET AUDIENCE: This continuing education activity is intended for physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES/OUTCOMES: After participating in this continuing education activity, the participant will: 1. Recognize the risks to ICU patients regarding PIs. 2. Select evidence-based strategies that can help prevent PIs. 3. Identify factors that can contribute to the development of PIs. 4. Choose collaborative approaches when working with a patient who has a PI. ABSTRACT: The literature on pressure injuries continues to expand at a rapid rate such that keeping current is a challenge for busy clinicians. In this article, the authors summarize six important articles related to pressure injuries published in 2020. The articles cover a range of topics including epidemiology, pathophysiology, prevention, and patient preferences for care. For each article, a description of the study results is provided along with a comment on why the results are important. This information should help clinicians incorporate these new data into their clinical practice.